Energy storages in diesel-electric icebreakers - Helenius, Henri (2012)
In this master's thesis the use of electrical energy storages for propulsion power balancing in icebreakers with diesel-electric propulsion power plant is studied. Ships that operate in ice are prone to get ice impacts to the propeller, which causes additional torque and slows the propeller down. In heavy and continuous ice contact, depending on the inertia and over torque capacity of the main engines, the propeller can slow down significantly. Even with diesel-electric machinery the power of the main engine(s) will drop suddenly. To keep the ship moving efficiently through the ice and to avoid getting stuck, the propulsion power must be restored quickly after the ice contact is over. The purpose of using electric energy storages is to balance out the load fluctuation experienced by the ship's propulsion plant, caused by ice block impacts on the propeller(s). This allows the prime mover s) to operate at constant power and optimum load. This reduces fuel oil consumption, emissions and wear and tear of the prime mover(s) as well as improves the acceleration and dynamic response of the vessel. The use of lead-acid and lithium-ion batteries as well as super capacitors and fuel cells is studied. Also the combination of two energy storages and the use of a brake resistor are investigated. The overall characteristics of the energy storages and the total cost of an energy storage system are compared to gained advantages in ship operation. A sensitivity analysis is included in the total cost analysis, where several profitability scenarios with changes in investment interest rate and fuel oil price increases are investigated. Available ice load measurement data is used to calculate and evaluate the required energy and power amount to successfully balance out the majority of the load fluctuations experienced by the ship's propulsion plant and reduce the greater load spikes. On the ground of the study, the optimal solution is chosen and the technical and economic feasibility of it is addressed. Tässä diplomityössä ...